EVALUATION OF CERVICAL ENCIRCLAGE IN REPEATED PREGNANCY LOSS - Riaz, G. Sarwar; Perveen, Tahira; Perveen, Ghazala (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: The concept of defective cervix resulting in habitual pregnancy loss was described as early as 17th Century. The recent concept of incompetent cervix in certain women with recurrent pregnancy loss was introduced only 35-ycars ago. Since then little progress has been made in clearly understanding the pathophysiology of cervical incompetence or in clearly defining its diagnosis. At present there are various surgical procedures involving cervical encirclage. Over the year’s various workers have done randomised prospective trials with the emphasis on various techniques and the advantages and disadvantages of each procedure. Most of these procedures involved a circlage around the cervix in some fashion.